Sequential Treatment of Superficial Basal Cell Carcinomas With Topical Methyl Aminolevulinate Photodynamic Therapy and Imiquimod 5% Cream: A Retrospective Study of Clinical and Cosmetic Outcomes. Issue 10 (October 2020) - Logan, Ian T.; Kulakov, Elizabeth L.; Perrett, Conal M.
Abstract : BACKGROUND: Topical photodynamic therapy (PDT) and imiquimod 5% (IMQ) cream are established treatments for superficial basal cell carcinoma (sBCC). Both have high initial response rates and recurrence rates of up to 37%. Recent studies demonstrate that PDT and imiquimod may act on sBCCs via synergistic immunomodulatory pathways. OBJECTIVE: To describe the sequential use of MAL-PDT and imiquimod 5% cream in the treatment of sBCCs and report treatment tolerability, cosmetic outcomes, and efficacy. MATERIALS AND METHODS: This is a retrospective case series of patients presenting over a 2-year period with primary sBCC who underwent 2 cycles of topical MAL-PDT, followed by 6 weeks of imiquimod 5% cream. Outcome measures were resolution of the index lesion at 3 months, side effects, cosmetic outcome, and long-term recurrence (LTR). RESULTS: A total of 17 consecutive patients ( n = 17) with a combined 21 sBCCs ( n = 21) were included. The median length of follow-up was 72 months (range 24–95 months). Long-term recurrence occurred in 2/21 lesions (10%). CONCLUSION: Sequential use of PDT and imiquimod was well tolerated with good cosmetic outcomes. The 10% LTR rate is at the lower end of the range reported for single modality treatment; however, larger samples are required to evaluate efficacy differences.